Using Paprika Extract in Chocolate Spread and White Compound Chocolate: Effects on Color Stability and Bioavailability - Göktaş, Hamza; Baycar, Abdullah; Konar, Nevzat; Yaman, Mustafa; Sağdıç, Osman; Yaman, Mustafa (Springer, 2023)
White compound chocolate (CC) and chocolate spread (CS) do not contain cocoa solids and thus they have deficiency of antioxidant activity. So, paprika extract (PE) was used to develop the visual and functional features of compound chocolate (CC) and chocolate spread (CS). Color stability of both chocolate samples was investigated for 12 weeks under accelerated shelf-life conditions and using PE significantly increased + a*, C*, and h° values of chocolate samples (P < 0.05). Also, at the end of shelf life, ΔE values were determined as > 2.83 and > 3.74 for CC and CS samples, respectively. Using PE in the production of CC and CS samples significantly increased antioxidant activity for pre-and post in vitro digestion, except for post digestion of S025 samples (P < 0.05). General acceptability of the CS samples decreased with increasing of PE ratios, for CC samples it was increased except for C100. The results showed that PE can be used in the production of functional chocolate with high antioxidant activity and as a natural coloring agent.
Keywords: Bioavailability; Chocolate; Color stability; Paprika; Sensory evaluation